2006
DOI: 10.4028/www.scientific.net/kem.324-325.1113
|View full text |Cite
|
Sign up to set email alerts
|

Fractography and Crack Initiation of Very-High-Cycle Fatigue for a High Carbon Low Alloy Steel

Abstract: Key words: fractography, very-high-cycle fatigue, crack initiation Abstract: Very-High-Cycle Fatigue (VHCF) is the phenomenon of fatigue damage and failure of metallic materials or structures subjected to 10 8 cycles of fatigue loading and beyond. This paper attempts to investigate the VHCF behavior and mechanism of a high strength low alloy steel (main composition: C-1% and Cr-1.5%; quenched at 1108K and tempered at 453K). The fractography of fatigue failure was observed by optical microscopy and scanning ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…For high-strength steels, cracks are prone to initiate at specimen subsurface or interior [9][10][11][12][13] in VHCF regime, and a distinct crack initiation feature of ''fish-eye" morphology embracing a region of ''fine-granular-area (FGA)" usually presents at fracture surface. Another typical feature of VHCF behavior for highstrength steels is that the S-N curve is a stepwise or duplex shape [14][15][16][17][18][19][20][21] with regard to surface-induced and interior-induced crack initiation, respectively. Bathias and Paris [22] investigated several high-strength steels via ultrasonic fatigue test technique and revealed that subsurface crack initiated from either nonmetallic inclusions or other microstructural inhomogeneities.…”
Section: Introductionmentioning
confidence: 99%
“…For high-strength steels, cracks are prone to initiate at specimen subsurface or interior [9][10][11][12][13] in VHCF regime, and a distinct crack initiation feature of ''fish-eye" morphology embracing a region of ''fine-granular-area (FGA)" usually presents at fracture surface. Another typical feature of VHCF behavior for highstrength steels is that the S-N curve is a stepwise or duplex shape [14][15][16][17][18][19][20][21] with regard to surface-induced and interior-induced crack initiation, respectively. Bathias and Paris [22] investigated several high-strength steels via ultrasonic fatigue test technique and revealed that subsurface crack initiated from either nonmetallic inclusions or other microstructural inhomogeneities.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the investigation of VHCF on metallic materials has attracted an increasing number of investigators in the fatigue research field (e.g. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]) due to the growing requirements of engineering applications, including aircraft, automobile, ship, railway, bridge, etc., for which the metallic components and structures need to endure a fatigue life larger than 10 7 or 10 8 loading cycles, and even requiring 10 10 -10 11 life cycles of endurance in some vital cases.…”
Section: Introductionmentioning
confidence: 99%
“…One typical characteristic of VHCF for high-strength steels is that the S-N curve includes two parts corresponding to subsurface and surface crack initiation, resulting in a stepwise or duplex shape [7][8][9]. Another distinct feature of crack initiation for VHCF is identified as a fisheye pattern on the fracture surface, which is mostly located at the specimen subsurface region and originates from a nonmetallic inclusion [3,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…INTRODUCTION ery-high-cycle fatigue (VHCF) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] of metallic materials is regarded as fatigue failure at stress levels below the conventional fatigue limit and the corresponding fatigue life beyond 10 7 loading cycles. Lots of modern engineering structures and components, such as airplanes, turbines, automobiles and high speed trains are expected to endure the safe performance in the range of 10 7 -10 10 load cycles.…”
mentioning
confidence: 99%